Modulating the ground state, stability and charge transport in OFETs of biradicaloid hexahydro-diindenopyrene derivatives and a proposed method to estimate the biradical character - Jousselin-Oba, Tanguy; Mamada, Masashi; Okazawa, Atsushi; Marrot, Jérome; Ishida, Takayuki; Adachi, Chihaya; Yassar, Abderrahim; Frigoli, Michel (Chemical science (Cambridge), 2020)
Biradicaloid compounds with an open-shell ground state have been the subject of intense research in the past decade. Although diindenoacenes are one of the most developed families, only a few examples have been reported as active layers in organic field-effect transistors (OFETs) with a charge mobility of around 10 −3 cm 2 V −1 s −1 due to a steric disadvantage of the mesityl group to kinetically stabilize compounds. Herein, we disclose our efforts to improve the charge transport of the diindenoacene family based on hexahydro-diindenopyrene (HDIP) derivatives with different annelation modes for which the most reactive position has been functionalized with (triisopropylsilyl)ethynyl (TIPS) groups. All the HDIP derivatives show remarkably higher stability than that of TIPS-pentacene, enduring for 2 days to more than 30 days, which depends on the oxidation potential, the contribution of the singlet biradical form in the ground state and the annelation mode. The annelation mode affects not only the band gap and the biradical character ( y 0 ) but also the value of the singlet-triplet energy gap (Δ E S-T ) that does not follow the reverse trend of y 0 . A method based on comparison between experimental and theoretical bond lengths has been disclosed to estimate y 0 and shows that y 0 computed at the projected unrestricted Hartree-Fock (PUHF) level is the most relevant among those reported by all other methods. Thanks to their high stability, thin-film OFETs were successfully fabricated. Well balanced ambipolar transport was obtained in the order of 10 −3 cm 2 V −1 s −1 in the bottom-gate/top-contact configuration, and unipolar transport in the top-gate/bottom-contact configuration was obtained in the order of 10 −1 cm 2 V −1 s −1 which is the highest value obtained for biradical compounds with a diindenoacene skeleton. Biradicaloid HDIP derivatives show that the Δ E S-T gap does not follow the reverse trend of the biradical character but depends more on the delocalization of the radical centres at the outer rings.